2017
DOI: 10.1590/1807-1929/agriambi.v21n11p752-757
|View full text |Cite
|
Sign up to set email alerts
|

Aggregate stability and penetration resistance after mobilization of a dystrocohesive Ultisol

Abstract: Evaluation of mobilized soil profiles can provide important information on soil compaction reduction processes. In this context, the objective of this study was to evaluate alterations in soil penetration resistance and the impact on the aggregate stability of a cohesive Ultisol cultivated with sugarcane. The experiment was carried out at the Carpina Sugarcane Experimental Station (EECAC/UFRPE), located in the city of Carpina, PE. Penetration resistance, mobilized area and depth, and percentage of soil aggrega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 9 publications
0
4
0
1
Order By: Relevance
“…The mean and standard deviation of PR in the vertical profiles of the 0-0.60 m layer are shown in Figure 2E. The increase in standard deviation with depth is because soil management under sugarcane cultivation typically results in homogenization of the surface layer, as reported by Tavares et al (2017). The plot shows that the lowest PR…”
Section: Resultsmentioning
confidence: 84%
See 3 more Smart Citations
“…The mean and standard deviation of PR in the vertical profiles of the 0-0.60 m layer are shown in Figure 2E. The increase in standard deviation with depth is because soil management under sugarcane cultivation typically results in homogenization of the surface layer, as reported by Tavares et al (2017). The plot shows that the lowest PR…”
Section: Resultsmentioning
confidence: 84%
“…The vertical PR profiles of different relief units are shown in Figure 2 Tavares et al (2017) suggested that PR is influenced by soil clay content and bulk density, which is associated with the volumetric content of water. Therefore, the greater PR homogeneity over depth in the type D relief unit is likely associated with the dynamics of water in soil since this relief unit had the lowest elevation (between 65 and 68 m).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Estos resultados corroboran parcialmente la segunda hipótesis planteada, debido a que la vinaza es una alternativa amigable y eficiente para disminuir la fertilización mineral y la contaminación ambiental, y son consistentes con los hallazgos de estudios experimentales previos respecto de que la aplicación de vinaza aumenta los niveles de Ca 2+ y Mg 2+ , así como de otros nutrientes como N, P y K + (Paulino et al 2011, Jiang et al 2012, Prado et al 2013, Andreotti et al 2015, Tavares et al 2017. Estos hallazgos indican que la adición de vinaza tiende a aumentar el contenido de cationes bases en suelos ácidos, lo que conduce a una mayor liberación de nutrientes para las plantas cultivadas en estas condiciones.…”
Section: Discussionunclassified